THE EU-JAPAN EPA AND THE QUESTION OF FORMAL AND INFORMAL TRADE BARRIERS FOR EUROPEAN BUSINESSES IN JAPAN - Erja Kettunen; Claes G. Alvstam (Trames, 2023)
This study focuses on how technical barriers to trade (TBT) are addressed in recent EU-Japan Economic Partnership Agreement (EPA). We analyze the pre- and post-EPA trade policies and the contested issues in Japan from the viewpoint of European businesses. An eclectic theoretical approach is adopted to study the economic, political and social aspects of trade barriers. Whereas formal trade barriers, such as tariffs and codified non-tariff barriers are easily discernible, the subtler informal trade barriers derive from social norms that guide administrative practices and are hard to measure, and largely neglected in recent research. Based on expert interviews, policy documents, and European business surveys, we observe that the enforcement of EPA in Japan lags behind concerning certain TBTs such as standards, approvals and testing. The findings suggest that informal trade barriers, often linked with investment barriers, have a bearing in the theorization on trade policies and free trade agreements.